Soft tissue-based registration of intraoral scan with cone beam computed tomography scan. Issue 2 (February 2022) - Deferm, J.T.; Nijsink, J.; Baan, F.; Verhamme, L.; Meijer, G.; Maal, T.
Abstract: The aim of this study was to evaluate a novel soft tissue-based method to register an intraoral scan (IOS) with a cone beam computed tomography (CBCT) scan. IOS and CBCT data were obtained from eight dentate patients (mean age 21 ± 2 years; three male, five female) and 14 fully edentulous patients (mean age 56 ± 9 years; eight male, six female). An algorithm was developed to create a soft tissue model of the CBCT scan, which allowed a soft tissue-based registration to be performed with the IOS. First, validation was performed on dentate jaws with registration of the palatal mucosal surface and accuracy evaluation at the level of the teeth. Second, fully edentulous jaws were registered using both the palatal and alveolar crest mucosal surfaces. Distance maps were created to measure the method accuracy. The mean registration error was 0.49 ± 0.26 mm for the dentate jaws. Registration of the fully edentulous jaws had a mean error of 0.16 ± 0.08 mm at the palate and 0.16 ± 0.05 mm at the alveolar crest. In conclusion, the high accuracy of this registration method may allow the digital workflow to be optimized when no teeth are available to perform a regular registration procedure.